Assessmentof tomato consumption and demand in Nepal - Ghimire, N.P.; Kandel, M.; Aryal, M.; Bhattarai, D. (Journal of Agriculture and Environment, 2018)
Tomato is also known as the poor man’s apple in Nepal. China is the largest producer of tomato in the world. Tomato is grown throughout the year in recent years in Nepal with the introduction of plastic house for off season production. Secondary information is used to assess the consumption pattern and national demand of tomato in 2015/16 for Nepal. The result showed the import from India is increasing compared to previous years. The reason behind this might be increase in consumption of tomato in recent years in Nepal. The central development region is the highest consumer of tomato compared to other regions of the country. The average national consumption of tomato was found 11.97Kg/person/year in Nepal.